2007
DOI: 10.1089/cpb.2007.9951
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Internet Addiction through the Lens of the Interpersonal Theory

Abstract: Previous studies have presented conflicting claims regarding reasons that people become addicted to the Internet. In this study, we attempted to identify predictors of Internet addiction based on Sullivan's interpersonal theory and Internet addiction literature. In our research model, it is hypothesized that good parent-child relationship positively correlates with good interpersonal relationships, which in turn are hypothesized to correlate with undesirable social anxiety. In addition, both parent-child and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
123
5
16

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(159 citation statements)
references
References 16 publications
15
123
5
16
Order By: Relevance
“…Furthermore, Jeong and Kim (2011) state that the amount and quality of social time spent with one's parents has effect on individuals' video game addiction. Regarding the literature, even though only a few number of studies on video game addiction and family relations have been conducted, there do exist studies which showing there to be a meaningful relation between internet addiction and family relations (Liu & Kuo, 2007;Mesch, 2003;Yen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Jeong and Kim (2011) state that the amount and quality of social time spent with one's parents has effect on individuals' video game addiction. Regarding the literature, even though only a few number of studies on video game addiction and family relations have been conducted, there do exist studies which showing there to be a meaningful relation between internet addiction and family relations (Liu & Kuo, 2007;Mesch, 2003;Yen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show there to be a meaningful relation between family relations, drug addiction (Johnson, McBride, Hopkins, & Pepper, 2014), and internet addiction (Liu & Kuo, 2007;Mesch, 2003;Yen, Yen, Chen, Chen, & Ko, 2007). In a study analyzing family's attitudes toward internet and internet addiction, it was found that families' negligent attitudes toward the internet itself played an important role in their children developing an addiction to the internet (Ayas & Horzum, 2013).…”
mentioning
confidence: 99%
“…However, there was contradictory evidence of high Self-Directedness and Cooperativeness profiles together with low scores on the Novelty Seeking and Self-Transcendence scales in another South Korean study (53). Internet addiction was positively associated with social anxiety and discontent with peer interactions (54), and with parenting attitudes, family communication, family cohesion, and family violence exposure (32).…”
Section: Factors Predictive Of Problematic Internet Usementioning
confidence: 99%
“…Araştırmalar anababalık stillerinin dışında anababa katılımının da özelde çocuk ve ergenlerin internet kullanımında (Warren, Gerke, & Kelly, 2002;Liu & Kuo 2007) genel olarak da, çocukların ve ergenlerin iyi oluşları üzerinde etkili olduğunu göstermektedir (Arim, Marshall, & Shapka, 2010;Barber, Stolz, & Olsen, 2005;Smetana & Daddis, 2002). Ergenler evde kendilerini güvende hissederlerse, anlaşıldıklarını düşünürlerse ve anababaları tarafından ciddiye alındıklarını düşünürlerse saplantılı internet kullanımı konusunda daha düşük düzeyde risk taşımaktadırlar (van den Eijnden ve diğ., 2010).…”
Section: İnternet Kullanımına Yönelik Anababalık Stilleriunclassified
“…Bu bulguya göre baba katılımı yüksek olan ergenlerin saplantılı internet kullanım davranışları gösterme eğilimleri daha düşüktür. Bu bulgu genel olarak baba katılımının çocukların ve ergenlerin iyi oluşları üzerinde etkili olduğunu gösteren (Kuzucu & Özdemir, 2013;Arim, Marshall, & Shapka, 2010;Barber, Stolz, & Olsen, 2005;Smetana & Daddis, 2002;van den Eijnden ve diğ., 2010) özelde de anababa katılımı ile çocukların internet kullanımı davranışları arasındaki olumsuz ilişkileri gösteren bulgularla benzerlik göstermektedir (Warren, Gerke, & Kelly, 2002;Liu & Kuo 2007). Bazı çalışmalar aile içindeki sorunların internet bağımlılığı riskini artırdığını gösterirken (Ko ve diğ., 2007;Yen ve diğ.…”
Section: Tartişma Ve Sonuçunclassified